2004
DOI: 10.1007/s00438-004-1079-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and diversity analysis of resistance gene analogues (RGAs) from cultivated and wild strawberries

Abstract: Degenerate oligonucleotide primers, designed based on conserved regions of Nucleotide Binding Site (NBS) domains from previously cloned plant resistance genes, were used to isolate Resistance Gene Analogues (RGAs) from wild and cultivated strawberries. Seven distinct families of RGAs of the NBS-LRR type were identified from two related wild species, Fragaria vesca and F. chiloensis, and six different Fragaria x ananassa cultivars. With one exception (GAV-3), the deduced amino acid sequences of strawberry RGAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Degenerate primers designed from conserved motifs of the nucleotide binding site-leucine rich repeat (NBS-LRR) class of R genes have been used to amplify R-like genes or resistance gene candidates (RGCs) from genomic DNA of numerous plants (Collins et al 1998;Noir et al 2001;López et al 2003;Martínez-Zamora et al 2004). Many of these RGCs are phylogenetically related with known R genes (Meyers et al 1999) and some of them have facilitated the cloning of full-length functional R genes from diVerent plant species (McDowell et al 1998;Zhao et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Degenerate primers designed from conserved motifs of the nucleotide binding site-leucine rich repeat (NBS-LRR) class of R genes have been used to amplify R-like genes or resistance gene candidates (RGCs) from genomic DNA of numerous plants (Collins et al 1998;Noir et al 2001;López et al 2003;Martínez-Zamora et al 2004). Many of these RGCs are phylogenetically related with known R genes (Meyers et al 1999) and some of them have facilitated the cloning of full-length functional R genes from diVerent plant species (McDowell et al 1998;Zhao et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In a more in-depth study, Plocik et al (2004) comparatively analyzed the RGHs within a specific family (Asteraceae) and indicated that gene duplication and loss events occur and change the composition of these gene subfamilies over time. Comparative analyses continued to be further applied in RGHs within a specific species, most of which concentrated on wild and cultivated plants such as apple (Lee et al 2003), strawberry (Martinez Zamora et al 2004), and potato (Kuang et al 2005). However, relatively few studies have comparatively analyzed RGH patterns between resistant and susceptible lines within a fruit tree species, and the behaviors of these RGHs during meiosis have been ignored.…”
mentioning
confidence: 99%
“…Zi-FL10 exhibited genetic changes due to either base substitutions and (or) small indels at the TaqI restriction sites, or relative large insertion by another fragment within the probe region, resulting in disappearance of the rice parental band (marked by a white arrow) and concomitant appearance of a novel larger band (marked by a black arrow) (D). Ekramoddoullah 2003; Lee et al 2003;Martinez-Zamora et al 2004).…”
Section: Discussionmentioning
confidence: 96%
“…For example, by analyzing a large number of RGAs isolated from different species of Grameneae, Leister et al (1998) documented that they have been evolving at a surprisingly rapid rate compared with other components of the grass genomes (Leister et al 1998). In contrast, in some non-grass plants, it was found that the evolution of RGAs is a gradual and slow process (Noir et al 2001;Liu and Ekramoddoullah 2003;Lee et al 2003;Martinez-Zamora et al 2004).…”
Section: Introductionmentioning
confidence: 89%